1997
DOI: 10.1152/jn.1997.77.2.874
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Saccadic Gain Adaptation in Rhesus Macaques

Abstract: We adapted the saccadic gain (saccadic amplitude/target step amplitude) by requiring monkeys to track a small spot that stepped to one side by 5, 10, or 15 degrees and then, during the initial targeting saccade, jumped either forward or backward by a fixed percentage of the initial step. Saccadic gain increased or decreased, respectively, as a function of the number of adapting saccades made in that direction. The relation between gain and the number of adapting saccades was fit with an exponential function, y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
194
5
6

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(250 citation statements)
references
References 16 publications
(8 reference statements)
45
194
5
6
Order By: Relevance
“…In general, the amplitude change produced by forward adaptation (15.4 Ϯ 3.8%) was less than that produced by backward adaptation as has been reported by others (e.g., Straube et al 1997). During a behavioral increase in saccade amplitude, we found no statistically significant changes in the number of spikes calculated by the comparison of either the sets of preand postadaptation trials (n ϭ 10) or the first and last 20 adaptation trials (n ϭ 2).…”
Section: Effect Of Amplitude Increase Adaptationsupporting
confidence: 60%
See 1 more Smart Citation
“…In general, the amplitude change produced by forward adaptation (15.4 Ϯ 3.8%) was less than that produced by backward adaptation as has been reported by others (e.g., Straube et al 1997). During a behavioral increase in saccade amplitude, we found no statistically significant changes in the number of spikes calculated by the comparison of either the sets of preand postadaptation trials (n ϭ 10) or the first and last 20 adaptation trials (n ϭ 2).…”
Section: Effect Of Amplitude Increase Adaptationsupporting
confidence: 60%
“…If thresholds were too low, we used target amplitudes that before adaptation were associated with large differences in discharge. We attempted to decrease saccade amplitude for open field neurons because amplitude increases are smaller and more difficult to induce (e.g., Straube et al 1997) so that associated changes in firing would be more difficult to discern. If the unit had a closed field, we mostly (11/14 neurons) attempted to increase saccade amplitude.…”
Section: Experimental Paradigmsmentioning
confidence: 99%
“…Furthermore, in accordance with previous accounts of head-restrained saccadic adaptation (Bahcall and Kowler 2000;Deubel 1991;Miller et al 1981;Noto et al 1999;Robinson et al 2003;Scudder et al 1998;Straube et al 1997), backward adaptation was larger in magnitude than forward adaptation in response to the same postsaccadic visual error. Phillips and colleagues (1997) showed that head-restrained saccadic adaptation transfers to head-unrestrained gaze shifts.…”
Section: Comparison With Head-restrained Adaptationsupporting
confidence: 90%
“…During visual orienting behaviors, this type of adaptation has been studied by introducing visual errors near the end of saccadic eye movements (Deubel 1987(Deubel , 1991Deubel et al 1986;McLaughlin 1967;Miller et al 1981;Noto et al 1999;Robinson et al 2003;Scudder et al 1998;Semmlow et al 1987;Straube et al 1997). When the head is prevented from moving, a shift in target location triggered by the beginning of a saccade leads initially to a visual error at the end of the movement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation